The Impact Of Canva-Assisted Problem-Based Learning (PBL) On Students' Learning Interest And Critical Thinking Skills In Fraction Topics Among Fourth-Grade Students At UPTD SDN Banyuates 1 Sampang - Puji Hastutik; Muhajir Muhajir; Sri Utami (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aims to determine the effect of implementing the Problem Based Learning (PBL) model assisted by Canva media on students' learning interest and critical thinking skills in fraction material for fourth-grade students at UPTD SDN Banyuates 1 Sampang. This study uses a quantitative approach with an experimental type and a pretest-posttest control group design. Data collection techniques were carried out through questionnaires to measure learning interest and tests to measure students' critical thinking skills. The data obtained were then analyzed using statistical tests including normality, homogeneity, and hypothesis testing. The results of the study indicate that there is a significant effect of the implementation of the Canva-assisted PBL model on students' learning interest and critical thinking skills. This is shown by the increase in scores after the treatment and the results of hypothesis testing which show a significance value of less than 0.05. Thus, the Canva-assisted PBL model is effectively used in mathematics learning in elementary schools, especially in fraction material.